RESPOND: a programme to prevent secondary falls in older people presenting to the emergency department with a fall: protocol for an economic evaluation. Issue 2 (20th October 2016) - Morello, R T; Morris, R L; Hill, K D; Haines, T P; Arendts, G; Redfern, J; Etherton-Beer, C D; Lowthian, J A; Brand, C A; Liew, D; Watts, J J; Barker, A L
Abstract : Background: Falls remain common for community-dwelling older people and impose a substantial economic burden to the healthcare system. RESPOND is a novel falls prevention programme that aims to reduce secondary falls and fall injuries among older people who present to a hospital emergency department (ED) with a fall. The present protocol describes a prospective economic evaluation examining the incremental cost-effectiveness of the RESPOND programme, compared with usual care practice, from the Australian health system perspective. Methods and design: This economic evaluation will recruit 528 participants from two major tertiary hospital EDs in Australia and will be undertaken alongside a multisite randomised controlled trial. Outcome and costing data will be collected for all participants over the 12-month trial. It will compare the RESPOND falls prevention programme with usual care practice (current community-based falls prevention practices) to determine its incremental cost-effectiveness according to three intermediate clinical outcomes: (1) falls prevented, (2) fall injuries prevented and (3) injurious falls prevented. In addition, utilities will be derived from a generic quality-of-life measure (EQ-5D-5L) and used to calculate the 'incremental cost per quality-adjusted life years gained'. Discussion: The results of this study will provide healthcare decision makers with evidence to assist with setting spending thresholds for preventive health programmes and inform selection of emergency and community service models of care. Trial registration number: The protocol for this study is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12614000336684 ); Pre-results.